THE EFFECT OF MARKETING COMMUNICATION MIX TOWARDS THE PURCHASE DE CISION OF MICE PRODUCTS: A CASE STUDY FROM SANTA MONICA HOTEL & CONVENTION IN BOGOR - Pratama, Yudhistira; Prasandya, Caroline Mutiara (Emerging Markets : Business and Management Studies Journal, 2018)
The MICE industry has been growing in Indonesia. With this potential, the lodging and accommodation businesses have a bright prospect of growth. Due to this matter, the accommodation industry is facing a tight competition, struggling to stand out from other establishments. Marketing communication mix has been proven to affect consumer?s buying behavior and simultaneously consumer?s purchase decision. This study investigates the effect of the five elements of marketing communication mix, namely advertising, personal selling, sales promotion, public relation, and direct marketing towards consumer?s purchase decision. The study is conducted at Santa Monica Hotel & Conference Bogor, a convention hotel that focuses on the MICE market. Questionnaires are distributed to 100 organizations that have held MICE activity at the hotel. The data is tested for validity, reliability, normality, heteroscedasticity, and multicollinearity. T-test and F-test is done to test the presence or absence of effect from each marketing communication mix elements towards purchase decision. The result shows that marketing communication mix does have simultaneous effect on purchase decision of MICE products, with personal selling and sales promotion as the elements that affect purchase decision. Advertising, public relation, and direct marketing does not show any effect towards purchase decision.